Diesel Degradation in Soil by Fenton Process - Villa, Ricardo D. [UNESP]; Trovo, Alam G. [UNESP]; Pupo Nogueira, Raquel F. [UNESP] (Soc Brasileira Quimica, 2010)
This work reports the use of Fenton process for diesel degradation and addresses common aspects of real situations that can affect the soil remediation efficiency. It was observed that most of diesel hydrocarbons containing less than 14 carbon atoms were lost by volatilization prior to the treatment. About 80% degradation was achieved in a loam soil, while less than 20% was observed in a clay loam soil. The multiple additions of H(2)O(2) resulted in 80% diesel degradation, while only 14% of diesel was degraded after a reaction time of 80 h using a single addition. The addition of soluble iron was essential to achieve high degradation levels. No significant increase in diesel degradation (t-test; P = 0.05) was observed using H(2)O(2) dosages between 0.09 and 0.36 g g(-1). Furthermore, the highest H(2)O(2) dosage applied (0.36 g g(-1)) degraded around 87% of the organic matter originally present in the soil.
Keywords: remediation; soil texture; fuel; hydrogen peroxide; short-chain alkanes